Antenatal diet and postpartum depressive symptoms: A prospective study. (July 2018) - Nathanson, Rivkah; Hill, Briony; Skouteris, Helen; Bailey, Cate
Highlights: Pregnancy diet is a risk factor implicated in the prevention of postpartum depressive symptoms. Antenatal fruit and vegetable intake were not associated with depressive symptoms 12 months post-birth. Antenatal fish intake was not associated with depressive symptoms 12 months post-birth. Future research should explore diet quality via adherence to dietary guidelines. Abstract: Postnatal depression is a critical public health concern, and gaining a better understanding of possible causes is paramount. Recently, diet quality during pregnancy has emerged as a possible preventative measure in ameliorating postnatal depression, however the evidence-base exploring this association is immature. The aim of this study was to examine the association between consumption of food groups characteristic of a quality diet during pregnancy (that is fruit, vegetable and fish intake) and postnatal depressive symptoms at 12 months postpartum. Pregnant women were recruited at 10–18 weeks gestation via advertising on online pregnancy forums, pregnancy and parenting magazines, and two Australian maternity clinics. Participants ( n  = 253) completed self-report questionnaires assessing fruit, vegetable and fish intake as well as depressive symptoms at early- to mid- pregnancy. Path analyses were conducted to examine whether fruit, vegetable and fish intake during pregnancy were associated with depressive symptom scores at 12 months postpartum. There were no associations between fruit, vegetable or fish intake in pregnancy and postnatal depressive symptoms. Antenatal diet quality as measured by intake of food groups associated with a healthy diet was not associated with postpartum depressive symptoms at 12 months postpartum. Future research should consider the exploration of dietary quality as a measure of overall adherence to evidence-based dietary guidelines.